Unicums, Fragments, and Other Hebrew Book Rarities - Heller, Marvin (Judaica Librarianship, 2014)
The subject matter of this article is unique or rare editions of early Hebrew books. Due to varying external circumstances, these rare books are extant only in fragments, unique single exemplars, or in a limited number of copies. Although Hebrew texts were subject to the same ravages of time and, perhaps, occasional indifference as were other early books, they also suffered to a much greater extent than their non-Hebrew counterparts from the indignities and deeds, or more accurately misdeeds, of anti-Semites who expended their wrath not only on Jews but also directed their venom towards Jewish books. The article is not about the causes of book rarity per se, but rather describes a variety of Hebrew works, either of the individual title, or, in some instances, of a particular edition of a reprinted work that is extant today in a single or a limited number of copies.